Revising and Validating the Community of Inquiry Instrument for MOOCs and Other Global Online Courses - Borup, Jered; Shin, Joan Kang; Powell, Marvin; Evmenova, Anya S.; Kim, Woomee (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2022)
Globally, online course enrollments have grown, and English is often used as a lingua franca for instruction. The Community of Inquiry (CoI) framework can inform the creation of more supportive, interaction-rich online learning environments. However, the framework and its accompanying validated instrument were created in North America, limiting researchers’ ability to use the instrument in courses where participants have varying levels of English language proficiency. We revised the CoI instrument so it could be more easily read and understood by individuals whose native language is not English. Using exploratory and confirmatory factor analyses (EFA and CFA) on data obtained from global online courses and MOOCs, we found the revised instrument had good fit statistics once seven items were removed. This study expands the usability of the CoI instrument beyond the original and translated versions, and provides an example of adapting and validating an existing instrument for global courses.